The long history of a melanoma associated with a congenital large plaque type blue nevus with subcutaneous cellular nodules - Francesco Savoia; Giuseppe Gaddoni; Giuseppe Re; Emilia Crisanti (Mattioli1885, 2015)
The term large plaque type blue nevus with subcutaneous cellular nodules (LPTBN-SN) refers to a huge blue nevus, usually located on the trunk, that develops subcutaneous nodules many years after the lesion has appeared. The potential malignancy of an LPTBN-SN was only discovered in 2012. We report the case of a 56-year-old Caucasian man that developed a cutaneous melanoma on an LPTBN-SN of the trunk. The first diagnosis was made more than 10 years before his death due to melanoma metastasis. The case reported here highlights the malignant potential of an LPTBN-SN, the very long course even without treatment and the possible coexistence of benign, borderline or malignant subcutaneous nodules in the same LPTBN-SN. Patients with large congenital blue nevi should be advised on the potential oncologic transformation of these lesions, the importance of follow-ups should be emphasized and, whenever possible, a preventive complete surgical removal should be evaluated before subcutaneous nodules develop.